2018
DOI: 10.3389/fmicb.2018.02462
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Endophytic Communities of Two Wild Rosa Varieties With Different Powdery Mildew Susceptibilities

Abstract: Powdery mildew (PM) is one of the most devastating and wide spread fungal diseases of rose, which seriously decrease its productivity and commercial value. In the present study, the endophytic fungal communities of two wild Rosa varieties (Rosa multiflora Thunb and R. multiflora var. carnea Redouté and Thory) with different PM susceptibilities were studied through Illumina MiSeq sequencer. A total of 14,000,424 raw reads were obtained from 60 samples, and 6,862,953 tags were produced after merging paired-end r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 63 publications
1
12
0
1
Order By: Relevance
“…Our results showed that the Shanon index of endophytic fungi in Q. serrata was significantly higher than that of Q. mongolica (Figure 3). This is consistent with previous findings that either endophytic fungi of diseaseresistant species had a higher diversity index compared with susceptible species to disease [36] or fungal endophytic community had a significant difference between pathogen-infected trees and healthy trees [10,37,38]. For instance, endophytic fungi colonized in Rosa multiflora had higher diversity than Rose multiflora var.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the Shanon index of endophytic fungi in Q. serrata was significantly higher than that of Q. mongolica (Figure 3). This is consistent with previous findings that either endophytic fungi of diseaseresistant species had a higher diversity index compared with susceptible species to disease [36] or fungal endophytic community had a significant difference between pathogen-infected trees and healthy trees [10,37,38]. For instance, endophytic fungi colonized in Rosa multiflora had higher diversity than Rose multiflora var.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the diversity of endophytic fungi associated with different species within the same genus can be abysmal, and even within the varieties of the same species, as already observed in Uncaria gambier gambir udang and gambir nasi varieties 17 , or in Rosa multiflora and var. carnea 18 .…”
mentioning
confidence: 99%
“…Differences were considered signi cant at P-values less than 0.05. The effects of different dosages Chinese herbal medicine on microbial core and unique OTUs in each soil environment were analyzed according to the method provided by Zhao 31 and Shade and Handelsman 32 . The OTUs that consistently appeared in the three biological replicates of all soil samples were regarded as core microbiomes, while the some OTUs that only presented in the three biological replicates of one soil samples were considered as unique microbiomes.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%